Assessing Appetitive Traits Among Chinese Young Adults Using the Adult Eating Behavior Questionnaire: Factor Structure, Gender Invariance and Latent Mean Differences, and Associations With BMI - He, Jinbo (Assessment, 2019)
The current study examined the factor structure, measurement reliability, measurement invariance across genders, and latent gender mean differences, of a new Chinese translation of the Adult Eating Behavior Questionnaire (C-AEBQ) in a Chinese young adult sample (n = 1,068, 52.57% women). The associations between the appetitive traits assessed by the AEBQ and body mass index were also explored. The previously established eight-factor model of the AEBQ was supported in the present sample. The C-AEBQ had strong measurement invariance between genders. Cronbach’s alpha estimates of the eight subscales of the C-AEBQ ranged from 0.76 to 0.97, and the test–retest reliability coefficients of the subscales ranged from 0.50 to 0.77. The C-AEBQ had adequate convergent and divergent validity, as supported by the theoretically expected correlations between C-AEBQ and the Three-Factor Eating Questionnaire. Furthermore, Satiety Responsiveness, Slowness in Eating, and Food Fussiness were inversely associated with body mass index. Overall, the C-AEBQ appears to be a psychometrically sound instrument as a comprehensive measure for appetitive traits for Chinese young adults.